Sarcoma of the thyroid region mimicking Riedel's thyroiditis. Issue 7 (1st July 2001) - Torres-Montaner, A; Beltrán, M; Romero de la Osa, A; Oliva, H
Abstract : Because sarcomas of the anterior lower neck region occur so infrequently, they are not usually considered in the differential diagnosis of Riedel's thyroiditis. Riedel's thyroiditis itself may be confused on clinical grounds alone with malignant neoplasms because of its invasive features. Sarcomatoid carcinoma is the main entity to be discarded in this regard. This is accomplished through histological examination by the finding of carcinomatous areas and/or reactivity with epithelial markers. These features also set apart sarcomatoid carcinoma from true sarcomas. This report concerns a patient with a sarcoma of the anterior lower neck region which was initially suspected to be Riedel's thyroiditis or sarcomatoid carcinoma on clinical and radiological grounds. A peroperative biopsy was interpreted by two independent pathologists as consistent with Riedel's thyroiditis. The subsequent clinical course and postmortem examination demonstrated a high grade sarcoma with metastasis to both lungs and the pleura, and invasion of adjacent neck structures. Nevertheless, some areas of the postmortem material showed a microscopic pattern similar to mediastinal fibrosis, raising the possibility of the malignant transformation of a fibrosclerotic lesion.